A comparison of high-speed internet service in Ghana: an analytical hierarchy approach. Issue 1 (5th February 2018) - Frimpon, Michael F.; Adaku, Ebenezer
Abstract : Purpose: The rising proportion of internet users in Sub-Saharan Africa and the lack of analytical techniques, as decision support systems, in choosing among alternative internet service providers (ISPs) by consumers underpin this study. The purpose of this paper is to propose an approach for evaluating high-speed internet service offered by ISPs in a sub-Saharan African country. Design/methodology/approach: Using a sample size of 150, pairwise comparisons of two ISPs along five criteria of cost, usability, support, reliability and speed were performed by ten person groups of university students working in various organizations in Ghana and undertaking an online Six Sigma Course. Geometric means were employed to aggregate the scores in 15 groups, and these scores were then normalized and used as input into an analytical hierarchy process grid. Findings: The results show that consumers of internet services highly emphasize the cost attribute of internet provision in their decision making. On the other hand, it was realized that consumers least emphasize the support provided by ISPs in their decision making among alternative ISPs. Originality/value: This study has sought to provide an analytical framework for assessing the quality of service provided by alternative ISPs in a developing economy's context. The evaluating criteria in this framework also reveal the key consumer requirements in internet service provision in a developing economy's environment. This, to a large extent, will inform the marketing strategies of existing ISPs in Ghana as well as prospective ones intending to enter the Ghanaian market. Besides, the National Communication Authority, a regulator of communication services provision in Ghana, will be informed about the performances of the ISPs along five performance criteria. This is expected to aid in their regulatory functions.